Relevansi Pemikiran Al-Kindi tentang Akal dan Ilmu Pengetahuan dalam Era Digital Saat Ini - Yhoseph bhaso; Nikodemus Rafael; Petrus Baptista Mola (Atmosfer: Jurnal Pendidikan, Bahasa, Sastra, Seni, Budaya, dan Sosial Humaniora, 2026)
He rapid advancement of digital technology has significantly transformed human life, particularly in the way information is accessed, processed, and distributed. While this development brings numerous benefits, it also generates serious challenges such as information overload, misinformation, and the decline of critical thinking skills among digital users. This study aims to examine the relevance of the philosophical thought of Al-Kindi on intellect (aql) and knowledge in addressing these contemporary issues within the digital era. The research employs a qualitative approach through library research, analyzing classical philosophical texts and contemporary scholarly works related to epistemology and digital literacy. The findings show that Al-Kindi positions intellect as the primary faculty of human beings in understanding truth and organizing knowledge systematically and rationally. According to Al-Kindi, knowledge must be grounded in logical reasoning to achieve certainty and clarity. In the context of the digital era, this perspective is highly relevant as individuals are required to critically evaluate vast and unfiltered information circulating in digital spaces. This study concludes that Al-Kindi’s rational philosophy provides a strong intellectual foundation for developing digital literacy, strengthening critical thinking skills, and promoting responsible engagement with technology in modern society.